PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KINERJA KARYAWAN DI PT. SINAR ANDALAS PROTEKSINDO - Indah Rahel Tenri Manik; Aldo Nanda Putra Pratama; Khomeiny Yunior (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to see the effect of: (1) work motivation on employee performance satisfaction (3) organizational commitment to employee performance satisfaction at PT.SINAR ANDALAS PROTEKSINDO. The research method uses quantitative quantitative research methods by looking at the relationship variable. By using simple data sampling technique, data analysis methods used are descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing either simultaneously or partially. The results of the calculation of hypothesis testing partially can be obtained the value of t value> t table or 0.379 <1.979 and significant obtained 0.0706> 0.05, tcount> ttable or 0.043> 1.979 and significant obtained 0.0668> 0.05, tcount> ttable or 3.174> 1.979 and significant obtained 0.002 <0 , 05 and the value of Fcount (9.248)> Ftable (1.69) and a significance probability of 0.000 <0.05. The coefficient of determination test results obtained Adjusted R Square value of 0.188, this means 18.8% of the variables that can be applied by the variation of the independent variables, while the remaining 18.8% is from other variables not examined in this study. The results showed that (1) the work environment has a positive effect on employee performance satisfaction (2) work motivation has a positive and significant effect on employee performance satisfaction (3) organizational commitment has no and insignificant effect on employee performance satisfaction simultaneously (work environment, work motivation motivation, and organizational commitment) have a significant effect on employee performance satisfaction at PT.Sinar Andalas Proteksindo.